แนวทางการพัฒนาและบริหารอาคารทางประวัติศาสตร์มาเป็นโรงแรมบูติคในเขตกรุงเทพฯ กรณีศึกษา โรงแรมจักรพงษ์วิลล่าและโรงแรมพระยาพาลาซโซ - กรณ์ธัญรินท์ บุญจงไพศรี (จุฬาลงกรณ์มหาวิทยาลัย, 2014)
As the number of foreign tourists have been continually increasing especially in Bangkok, which has been awarded The World’s Best City Award for four consecutive years and many tourist attractions are located in the area of Ratanakosin, entrepreneurs have seen the potentiality of boutique hotels. There are also many countries developing and managing historic buildings as boutique hotels such as This thesis aims at studying 1) the process in developing and managing historic buildings as boutique hotels 2) the problems and solutions before/during/after the developing process and the management of boutique hotels with regard to the physicality, management, member staff, marketing, service and finance. Data are collected from the interview with the executives of both hotels and related experts including document research, research and field study of the case studies’ physicality. The research results show that both hotels have different ways of development and management. Chakrabongse Villas have been developed using the reconstruction format by building new Thai wooden houses to replace the original ones and keeping the original location and plan. On the other hand, Praya Palazzo has been developed using the rehabilitation format by renovating old buildings to suit present needs while trying to keep the original building, materials and colors as much as possible with suggestions from the Fine Arts Department. The service of Chakrabongse Villas is in Bed & Breakfast style during office time which suits the need of European travelers who are familiar with this style while Praya Palazzo has 24-hour service. The similarity is that both hotels are initiated with historic buildings as the product lead. The project owner has already researched that the target customers are educated European travelers who like cultural travel, work in the management level and have the ability to pay. The buildings are then designed and decorated with ancient Thai style focusing on niche market customers. Both hotels are managed by their owners who have visions in cultural conservation. The organizations are managed according to the member staffs’ duties. They are both small and not complicated. These are the advantages for improving the management system and quickly serving the customers’ needs without passing many steps. Detailed service and completed facilities are offered. Both hotels have no budget for marketing and the rooms are sold mainly through OTA. All investment money is from private money and fundraising from partners. It is also found that the owners have background knowledge and are interested in arts. They are inspired to revive the buildings without making too much profit but focusing instead on adding values to historical buildings. This is suitable for the project owners who are the landlords themselves as it is a way to add value to the assets and also an opportunity to create income for the owners.